Development of a Learning Model Using Practical Unit Modules for Electrical Installation at SMK Negeri 3 Makassar - Ratih Puspita Siwi Siwi; Andi Alviadi Nur Risal (JURNAL PENDIDIKAN BAHASA DAN BUDAYA, 2025)
Module is one of the teaching materials that can be used by students, either independently or with the assistance of a teacher. Therefore, it is important to develop modules so that they can function optimally as effective learning guides for students. The objective of this study was to develop a practical learning module for electrical installation. The research employed the Research and Development (R&D) method. The stages of the research included: (1) identifying potentials and problems, (2) data collection, (3) product design, (4) product validation, (5) product revision, (6) product testing, (7) further revision, and (8) analysis and reporting. The research design used was Pretest-Posttest Control Group Design. Based on the validity aspects, the results of the development of the practical module for electrical installation are as follows: (1) practical module 1 obtained a score of 85.86% and was categorized as valid; (2) practical module 2 obtained a score of 87.75% and was categorized as valid; and (3) practical module 3 obtained a score of 86.31% and was categorized as highly valid. Student learning activities using the practical electrical installation module were significantly higher compared to students who used worksheets (LKS). Learning outcomes in the cognitive, affective, and psychomotor domains of students who used the practical module were significantly higher than those who used worksheets, with a significance value of 0.001.